Distribution network planning and inventory management in a multi-retailing supply chain. Issue 1 (April 2021) - Ji, Jindi; Wang, Yuxin; Jia, Haitao; Shi, Mingjun
Abstract: A In this paper, we are aimed at discussing problems of distribution network planning and inventory management in a multiple-retailing supply chain. We study the distribution model and inventory management model, integrating both models to analyse the optimal decisions on maximum profit. The main methodology we used is literature study and model formulations. Through the research, we finally present the optimal distribution and inventory decision.